Branding the Local: Anti-corporate Resistance in Online Consumer Reviews - Kuehn, Kathleen M (AoIR Selected Papers of Internet Research, 2013)
A textual analysis of consumer evaluations on Yelp.com (n=1,972) interrogates the form and function of discursive resistance deployed by consumer reviewers. Findings reveal that consumers regularly articulate a politics of consumption at the local level, namely through the explicit celebration of “localism.” In promoting local consumption, anti-corporate discourses also function to resist cultural homogenization in users’ [offline] communities. Here, reviews serve the function of redirecting economic flows away from corporate-owned business towards (ambiguously defined) “independent” establishments, even as a form of social responsibility. Ultimately, however, localism is discursively constructed (and in some ways performed) as a consumable aesthetic that operates no differently from the corporate “brand logic” that these very reviews contest. Read against Jodi Dean’s work on communicative capitalism, Yelp’s anti-corporate/pro-local discourse fits squarely within the depoliticizing effects of neoliberalism’s project of empowered consumption, raising a number of questions about what larger political economic changes consumer reviews can effect.